Air Services at Australian Cities: Change and Inertia 2005–2010. (14th June 2012) - FUELLHART, KURT; O'CONNOR, KEVIN
Abstract This research analyses international and domestic air services in Australia during a six year period, 2005–2010. We place air services into their urban context by relating them to city‐based measures such as population, tourism, and producer services employment among other measures. The research takes a supply‐side approach in an assessment of international and domestic capacity at major Australian airports from the perspective of the number of seats, the nature of links, and competition. Multiple linkage analysis and the concept of effective competitors allow us to explore this perspective at greater depth. Our findings show substantial changes in international patterns, specifically favouring Melbourne, Perth, and Gold Coast. In contrast, the domestic scene is characterised by little change, an outcome we link to the underlying stability in the settlement system and the location of some major economic activities. While the results are related to our measures of urban characteristics, some special region‐specific aspects are also at work. Finally, in both the international and domestic cases we find evidence of greater airline diversity which may benefit consumers.